The worker branch in Yorkshire as a way of organising Polish migrants: exploring the process of carving out diasporic spaces within the trade union structure. Issue 15 (17th September 2020) - Ciupijus, Zinovijus; MacKenzie, Robert; Forde, Christopher
ABSTRACT: While post-2004 Polish labour migration to the UK was underpinned by diasporic spaces instrumental in facilitating social and labour market adjustments, the institutions of the host society such as trade unions also sought to establish links with migrants. The analysis of interactions between UK unions and EU migrants focused on organising strategies and specific provisions such as English language learning. However, the discussion tended to ignore the impacts of diasporic influences, from ethnicity and native languages of migrants to the outcomes of migrant worker organising. Drawing on ethnographic and qualitative data, this paper discusses how Polishness, in its ethnic, historic and linguistic manifestations, has affected the internal dynamics of a migrant worker organisation created by a major UK trade union. The explicit acknowledgement of diasporic particularities of post-2004 Polish migrants not only enabled labour organising activities but also shaped the migrant worker organisation from within. The strength of diasporic influences on one hand and the chosen form of union organising on the other created conditions for the development of diasporic spaces within the institution of the host society.